MAINTAINING MULTICULTURAL SOCIETY IN THE MALAY WORLD OF INDONESIA: STRATEGIC AGENDA - Ismail Sukardi (Universitas Islam Negeri Raden Fatah Palembang, 2017)
The fact that Indonesia's Malay world is a very multicultural country is often the reason for the emergence of various conflicts in the name of ethnicity, religion, and race (SARA), such as the Poso, Ambon, Papua, Kalimantan, Ahmadiyah, and so on. This paper explains about various efforts that can be sought to maintain stability and harmony in pluralism of Indonesian Malay world. Existential awareness as a multicultural nation is a social and ideological capital that must continue to be grown, developed, and maintained so that Indonesia is more just, prosperous, safe, peaceful, and prosperous. Therefore the strategic agenda that must be carried out is to encourage increased strategic role of religious leaders, encourage the growth of mutual understanding between religious communities, seek social cooperation between religious groups, promote multicultural education, and incorporate elements of democratic principles and human rights (HAM) in curriculum.